Hubungan Kualitas Visual Lanskap dan Tingkat Pengalaman Pengunjung Obyek Wisata Alam Kalibiru, Kabupaten Kulon Progo - Retno Nur Utami; Kaharuddin Kaharuddin; Mukhlison Mukhlison; Ferrieren Curassavica Arfenda (Jurnal Ilmu Kehutanan, 2021)
The number of visitors to Kalibiru Nature Tourism Object in Kulon Progo Regency during weekends has exceeded its effective carrying capacity. Distributing the visitors on weekdays could become one of the solutions to prevent ecological damage. This research aimed at better understanding the relationship between visual landscape quality and the level of visitors’ experience in Kalibiru Nature Tourism Object, Kulon Progo Regency. Two independent surveys were conducted, one during the weekdays' dan another one during the weekends in which 100 respondents were randomly selected for each survey. This research employed descriptive analysis, t-test for independent samples, and simple linear regression. The results showed that there is no significant difference between the average score of landscape visual quality between weekdays (score 75.44) and weekends (score 78.01). Similarly, there is also no significant difference between the level of visitors’ experience during weekdays (score 78.09) and weekends (80.34). The simple linear regression analysis indicated that the landscape visual quality has a positive influence on the level of visitors’ experience in both categories.